CLASSIFICATION OF CHILD GROWTH AND DEVELOPMENT DISORDERS USING SUPPORT VECTOR MACHINE (SVM) - Ridho Tri Soekmanegara; Raissa Amanda Putri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Child developmental disorders are conditions that may affect children's cognitive, behavioral, social, and communication abilities. Early identification of developmental disorders is essential to ensure timely intervention and appropriate treatment. However, the classification of developmental disorders remains challenging due to the similarities of symptoms among different disorders. Therefore, this study aims to implement the Support Vector Machine (SVM) algorithm for the classification of child developmental disorders, specifically ADHD, Autism Spectrum Disorder and Down Syndrome. This study employed a quantitative approach using a dataset consisting of 1,786 records with nine predictor attributes related to developmental symptoms. Data preprocessing was performed through missing value handling using the Most Frequent Imputation method and label encoding. The dataset was divided into training and testing sets using an 80:20 ratio. The SVM model was developed using the Radial Basis Function (RBF) kernel and evaluated using a confusion matrix, accuracy, precision, recall, and F1-score metrics. The experimental results demonstrated that the proposed SVM model achieved an accuracy of 98.88%. The classification report showed high performance across all classes, with precision, recall, and F1-score values reaching 0.99 on average. Confusion matrix analysis indicated only four misclassified instances out of 358 testing samples, while the Down Syndrome class achieved perfect classification performance. The findings indicate that the SVM algorithm is highly effective for classifying child developmental disorders and has the potential to support early identification and decision-making processes in child healthcare. The proposed model can serve as a reliable decision-support tool for healthcare professionals and parents in detecting developmental disorders based on observed symptoms. Keywords: SVM, Machine Learning, Developmental Disorders, ADHD, Autism, Down Syndrome, Classification. Abstrak: Gangguan perkembangan anak merupakan kondisi yang dapat memengaruhi kemampuan kognitif, perilaku, sosial, dan komunikasi anak. Identifikasi dini terhadap gangguan perkembangan sangat penting untuk memastikan intervensi yang tepat waktu dan penanganan yang sesuai. Namun, klasifikasi gangguan perkembangan masih menjadi tantangan karena adanya kemiripan gejala di antara berbagai jenis gangguan. Oleh karena itu, penelitian ini bertujuan untuk mengimplementasikan algoritma Support Vector Machine (SVM) dalam klasifikasi gangguan perkembangan anak, khususnya Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), dan Down Syndrome. Penelitian ini menggunakan pendekatan kuantitatif dengan memanfaatkan dataset yang terdiri dari 1.786 data dan sembilan atribut prediktor yang berkaitan dengan gejala perkembangan anak. Tahap prapemrosesan data dilakukan melalui penanganan nilai yang hilang menggunakan metode Most Frequent Imputation serta proses label encoding. Dataset kemudian dibagi menjadi data pelatihan dan data pengujian dengan rasio 80:20. Model SVM dikembangkan menggunakan kernel Radial Basis Function (RBF) dan dievaluasi menggunakan confusion matrix, accuracy, precision, recall, serta F1-score. Hasil eksperimen menunjukkan bahwa model SVM yang diusulkan mampu mencapai tingkat akurasi sebesar 98,88%. Laporan klasifikasi memperlihatkan kinerja yang sangat baik pada seluruh kelas dengan nilai rata-rata precision, recall, dan F1-score mencapai 0,99. Analisis confusion matrix menunjukkan hanya terdapat empat kesalahan klasifikasi dari total 358 data pengujian, sementara kelas Down Syndrome berhasil diklasifikasikan secara sempurna tanpa kesalahan. Temuan penelitian ini menunjukkan bahwa algoritma SVM sangat efektif untuk mengklasifikasikan gangguan perkembangan anak dan memiliki potensi besar dalam mendukung proses identifikasi dini serta pengambilan keputusan di bidang kesehatan anak. Model yang diusulkan dapat digunakan sebagai alat bantu pengambilan keputusan yang andal bagi tenaga kesehatan maupun orang tua dalam mendeteksi gangguan perkembangan anak berdasarkan gejala yang diamati. Kata Kunci: Support Vector Machine (SVM), Machine Learning, Gangguan Perkembangan Anak, ADHD, Autisme, Down Syndrome, Klasifikasi.